PRINSIP HIDUP KAWRUH BEGJA DALAM PERSPEKTIF ANTON BAKKER - Marsono (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2019)
This article outline aims to understand the principle of life in this kind of Javanese society based on Anton Bakker’s metaphysical theory. Describes the position of the Javanese as being there among other creators in a structure of reality. Javanese people in this context are assumed to have metaphysics, namely placing themselves as subjects as well as objects of metaphysics, and occupying a position as a being for themselves as well as being for others. The principle of kawruh thus is more dominant showing mental aspects in the form of the soul but, it is emphasized again that the soul and the body remain a unity of reality inseparable with their respective roles. The Javanese do not merely look at reality through their own perspective, but also look at the physical reality of the world outside themselves, then see the range of connectedness between themselves and the reality outside themselves.